HvHOX9, a novel homeobox leucine zipper transcription factor, positively regulates aluminum tolerance in Tibetan wild barley - Feng, Xue (Journal of experimental botany, 2020)
© The Author(s) 2020. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved. For permissions, please email: journals.permissionsoup.com.